Effects of effective microorganisms on properties of blended cement concrete - 1985-; Abdul Rahman Mohd. Sam; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017